Wheeling and Dealing in War: Smuggling, Stigma and Separatist Rebellions - Mandić, Danilo (PARTECIPAZIONE E CONFLITTO, 2022)
Organized crime is both a liability and an asset for rebel movements. Illicit channels of supply – notably for arms and fuel – are often the only possible ones. Yet, this can come at the costs of political de-legitimization. The state resisting violent separatism as well as adherents or bystanders may consider separatists illegitimate for associating with readily-vilified criminal actors, and rebel groups cannot publicly embrace it without opprobrium. But why are some separatists stigmatized more than others for their criminal alliances? This article focuses on separatist rebel movements in order to explore the unique challenges of legitimacy and stigma that smuggling poses. Based on a comparative analysis of six case studies, I analyze variance in the legitimacy costs associated with criminal practices. I argue that the stigmatization of organized criminal smuggling in separatist governance depends on whether the smuggling is symmetrical, matched and shared by host state institutions, or asymmetric, unmatched by and unrelated to the host state.